Redescription of the holotype of Chanaresuchus bonapartei Romer, 1971 (Archosauriformes: Proterochampsidae) from the Upper Triassic rocks of the Chañares Formation of north-western Argentina. (1st September 2020) - Trotteyn, M. Jimena; Ezcurra, Martín D.
Abstract : Proterochampsids are one of the several diapsid groups that originated, flourished and became extinct during the Triassic Period. The current fossil record of this group indicates that its species were restricted to continental assemblages of the early Late Triassic of South America. The recent description of new rhadinosuchine proterochampsid specimens from the Chañares Formation (early Carnian, Argentina) increased the morphological diversity of the group and cast doubts on their current taxonomic scheme. Previous authors have pointed out that available diagnoses do not allow specimens to be referred unambiguously to the different rhadinosuchine species. Here we redescribe, figure and compare in detail the holotype of one of these rhadinosuchine species, Chanaresuchus bonapartei from the Chañares Formation. The new information provided here allows us to discuss the degree of post-mortem deformation present in the specimen and check the character scorings for the proterochampsid species sampled in the most comprehensive phylogenetic data set currently available for Permo–Triassic archosauromorphs. Our new cladistic analyses find stronger support than previous studies for the monophyly of Rhadinosuchinae and the clades that include Doswelliidae + Proterochampsidae and Tropidosuchus + Rhadinosuchinae. Doswelliids are recovered within Proterochampsidae, as the sister taxon to the genus Proterochampsa, in some analyses under implied weights. Some characters present a phylogenetic signal consistent with the latter grouping, but one additional step is required to force it in the analysis under equal weights. We consider that the new anatomical and phylogenetic information provided here is a step towards a necessary taxonomic revision of Rhadinosuchinae and further research on the interrelationships of proterochampsian archosauriforms.